Fatal and Rapid Progressive Isolated Cerebral Mucormycosis Involving the Bilateral Basal Ganglia: A Case Report - Zhang, Gao-jia; Zhang, Shao-ke; Wang, Zan; Zhu, Yi-xin; Kong, Jun; Huang, Li-li; Guo, Yi-jing; Wang, Yan-juan; Zou, Rong-cheng; Xie, Chun-ming (Frontiers in Neurology, 2020)
Isolated cerebral mucormycosis is a clinical type of mucormycosis that is estimated to account for 8% of all mucormycosis cases. The clinical symptoms of isolated cerebral mucormycosis are elusive, and thus conventional techniques often lake sensitivity and specificity. Moreover, cultures are often negative, even when direct microscopy examination is positive. Although histopathology will probably remain the gold standard for the diagnosis of mucormycosis, obtaining a biopsy specimen is not always feasible in most vulnerable populations. Thus, molecular approaches are currently used as an advantageous assistant examination method to improve the early identification of the causative agent and subsequently guide therapy to improve the prognosis of patients. Here, we report a case of isolated cerebral mucormycosis caused by Rhizopus microspores in a healthy young adultthat was identified using next-generation sequencing technology.